Electronic Customer Relationship Management and Electronic Service Quality as Antecedents of Customer Retention - Fauziyah, Fauziyah; Ramadhinda, Hannisa; Munawaroh, Munjiati (Universitas Muhammadiyah Yogyakarta, 2022)
The number of internet users in Indonesia is increasing every year. One of the activities that most users do on the internet is e-commerce. There are many e-commerce service providers in Indonesia. A survey conducted by the Indonesian Internet Service Providers Association (APJII) proves that Tokopedia has the highest number of visitors, up to 157.1 million. It can be a market opportunity for the company. The emergence of many competitors in the marketplace requires research on electronic CRM, electronic service quality, and customer retention. This study aims to analyze the effect of Electronic Customer Relationship Management and Electronic Service Quality on Customer Retention. Research on E-CRM and E-SERVQUAL obtained varied results, especially those conducted in the marketplace in Indonesia. The subjects were customers who had made online transactions at Tokopedia with purchase intensity at least twice in the last six months. The sample of 200 respondents was analyzed using Structural Equation Model (SEM) through the AMOS program. The result shows that electronic customer relationship management and electronic service quality positively and significantly affect customer retention.